2012
DOI: 10.1016/j.jcin.2012.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Incidence and Predictors of Stent Thrombosis and Other Major Adverse Cardiac Events in the Year After XIENCE V Implantation

Abstract: In this large, real-world population, XIENCE V demonstrated low event rates at 1 year, with several independent predictors. Early DAPT interruption (≤ 30 days) was the most potent predictor of ST, whereas delayed interruption (>30 days) was not predictive. (XIENCE V Everolimus Eluting Coronary Stent System [EECSS] USA Post-Approval Study; NCT00676520).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 28 publications
4
46
1
Order By: Relevance
“…1,7-9, 11 We also previously reported the favorable impact of IVUS-guided stenting on 1-year outcomes in ADAPT-DES. 16 In the present study, IVUS-guided stenting remained a significant predictor of freedom from 2-year ST, consistent with previous data.…”
Section: Modifiable Risk Factors For Stmentioning
confidence: 89%
“…1,7-9, 11 We also previously reported the favorable impact of IVUS-guided stenting on 1-year outcomes in ADAPT-DES. 16 In the present study, IVUS-guided stenting remained a significant predictor of freedom from 2-year ST, consistent with previous data.…”
Section: Modifiable Risk Factors For Stmentioning
confidence: 89%
“…11,13,18,22 Krucoff et al 18 demonstrated the absence of ST with DAPT interruption beyond 6 months after CoCr-EES implantation from a postmarket surveillance study of 5054 real-world patients. Kedhi et al 16,22,23 reported from a pooled analysis of 4 randomized trials that DAPT discontinuation beyond 6 months after CoCr-EES implantation may be safe.…”
Section: Discussionmentioning
confidence: 99%
“…In a large registry study of patients receiving CoCr-EES, discontinuation of DAPT before 30 days was associated with an increased rate of ST 13 ; this study did not, however, examine the rates of ST as a function of DAPT discontinuation in circumscribed risk periods after 30 days. We therefore analyzed the relationship between ST and DAPT use through 2 years in a large, pooled sample of patients from the CoCr-EES Xience V family of clinical studies.…”
Section: Généreux Et Al Stent Thrombosis and Dapt Interruptionmentioning
confidence: 99%
“…It is known that the stented length is a strong predictor of events at follow-up, such as stent thrombosis and need for repeat revascularization. 53,54 Additionally, the permanent caging of the artery inhibits the recovery of the physiological properties of the vessel. In CTO PCI, BVS could have obvious advantages compared with metallic stents by fully avoiding the problems arising from having permanent metal caging in the vessel.…”
Section: Bvs In Chronic Total Occlusionsmentioning
confidence: 99%